Identifying training deficiencies in military pilots by applying the human factors analysis and classification system - Li, Wen-Chin; Harris, Don (Ablex Publishing Corporation, 2013)
Without accurate analysis, it is difficult to identify training needs and develop the content of training programs required for preventing aviation accidents. The Human Factors Analysis and Classification System (HFACS) is based on Reason’s system-wide model of human error. In this study 523 accidents from the R.O.C. (Republic of China) Air Force were analyzed in which 1,762 human errors were categorized. The results of the analysis showed that errors of judgment and poor decision-making were commonly reported amongst pilots. As a result it was concluded that there was a need for military pilots to be trained specifically in making decisions in tactical environments. However, application of HFACS also allowed the identification of systemic training deficiencies within the organization further contributing to the accidents observed.
Keywords: Accident Investigation, Error Analysis, Human Error, Human Factors Analysis and Classification System (HFACS), Training Development